Radiographically Negative, Asymptomatic, Sentinel Lymph Node Positive Cutaneous T-Cell Lymphoma in a 3-Year-Old Male: A Case Report - Jeffrey Carson; Jiri Bedrnicek; Shahab Abdessalam (Case Reports in Pediatrics)
We present a case of a 3-year-old male originally diagnosed with a CD30+ anaplastic cutaneous T-cell lymphoma with no evidence of systemic disease after CT scan, PET scan, and bone marrow aspiration. Sentinel lymph node biopsy (SLNB) was performed as an additional step in the workup and showed microscopic disease. Current management/recommendations for cutaneous T-cell lymphoma do not include SLNB. Medical and surgical management of cutaneous malignancies is dramatically different for local versus advanced disease. Therefore adequate evaluation is necessary to properly stage patients for specific treatment. Such distinction in extent of disease suggests more extensive therapy including locoregional radiation and systemic chemotherapy versus local excision only. Two international case reports have described SLNB in cutaneous T-cell lymphoma with one demonstrating evidence of node positive microscopic disease despite a negative metastatic disease workup. This case is being presented as a novel case in a child with implications including lymphoscintigraphy and SLNB as a routine procedure for evaluation and staging of cutaneous T-cell lymphoma if the patient does not demonstrate evidence of metastatic disease on routine workup.